Analisis Yuridis Perkembangan Tindak Pidana Pencucian Uang Saat Ini Sebagai Upaya Pencegahannya Di Indonesia - Saptono, Saptono; Hadiyanto, Alwan; Ciptono, Ciptono (JURNAL USM LAW REVIEW, 2024)
The aim of this study is to study efforts to prevent the criminal practice of money laundering in Indonesia. Research on the prevention of money laundering crime in Indonesia is critical and urgent, given the huge impact it has on the economy and national security. Money laundering not only undermines the integrity of the financial system, but is also often associated with other crimes such as corruption, drug trafficking, and terrorist financing, which can threaten social and political stability. The research has made an important contribution to strengthening the TPPU prevention system and raising awareness of the urgency of combating money laundering crimes in order to maintain economic stability and national security. This research uses normative research methods and uses secondary data. The prevention of TPPU in Indonesia is a very important and urgent matter. The impact of the TPPU not only undermines the integrity of the financial system, but is also potentially linked to other crimes such as corruption, drug trafficking, and the financing of terrorism, which can threaten the country's social and political stability. Effective prevention strategy but also synergy between the Government, the DPR, and PPATK. Prevention steps with the principles of Costumers Due Diligence Principle and the Know Your Customer system as one of the ways of TPPU prevention.   Tujuan dari penelitian ini adalah untuk mengkaji upaya pencegahan praktik tindak pidana pencucian uang (TPPU) di Indonesia. Penelitian tentang pencegahan tindak pidana pencucian uang di Indonesia sangat penting dan mendesak, mengingat dampak besar yang ditimbulkannya terhadap ekonomi dan keamanan nasional. Pencucian uang tidak hanya mengganggu integritas sistem keuangan, tetapi juga sering terkait dengan kejahatan lain seperti korupsi, perdagangan narkotika, dan pembiayaan terorisme, yang dapat mengancam stabilitas sosial dan politik. Penelitian ini memberikan kontribusi penting dalam memperkuat sistem pencegahan TPPU dan meningkatkan kesadaran akan urgensi memerangi kejahatan pencucian uang guna menjaga stabilitas ekonomi dan keamanan nasional. Penelitian ini menggunakan metode penelitian normatif dan menggunakan data sekunder. Upaya pencegahan TPPU di Indonesia merupakan hal yang sangat penting dan mendesak. Dampak dari TPPU tidak hanya mengganggu integritas sistem keuangan, tetapi juga berpotensi terkait dengan kejahatan lain seperti korupsi, perdagangan narkotika, dan pembiayaan terorisme, yang dapat mengancam stabilitas sosial dan politik negara. strategi pencegahan yang efektif tetapi juga adanya sinergi antara  Pemerintah, DPR, dan PPATK.  Langkah pencegahan dengan prinsip Prinsip Costumers Due Diligence Principle dan sistem Know Your Customer sebagai salah satu cara pencegahan TPPU.